Analisis Taktik Pertandingan Pencak Silat Kategori Tanding - Mujahid, Hamzah; Subekti, Nur (Journal Coaching Education Sports, 2021)
The purpose of this study is to determine the structure of the tactical actions of the pencak silat match in the sparring category as well as the differences based on the match rounds and match results. based on match rounds and match results. The research method used a quantitative approach based on observation-survey on 98 athletes in 48 final matches in three elite level pencak silat championships; National Sports Week, Sea Game, Asian Games. Data collection was through observation of match videos, recording all tactical actions (attack, defense, block).(attack, defense, block) and analyzed using SPSS. Based on the round of the match, there were differences in the actions of attacking and defending sig values < p 0.05 between rounds 1-2 and 1-3, but between rounds 2-3 no difference was found sig value > p 0.05. As for action blocks found no difference in sig value > p 0.05 between rounds 1-2-3. In terms of match results, differences were found with a sig value < p 0.05 in the action of attacking and defending tactics; winners tend to utilize the ability of defense, while non-winners tended to perform attacking actions, while the block actions of winners and non-winners were relatively balanced. non-winners were relatively balanced. The results of the study can be a reference for martial arts coaches and practitioners in organizing tactics training sessions considering changes in action organizing tactics training sessions considering changes in the actions of each round of the match.